Kontestasi Agama, Pasar dan Negara dalam Membangkitkan Daya Saing Ekonomi Umat melalui Sertifikasi Halal - Masruroh, Nikmatul; Shahrin, Attori Alfi (Proceedings of Annual Conference for Muslim Scholars, 2022)
This paper purposes are firsly; describe the presence of the obligation of halal certification for the economy of the people. The second, to analyze the effectiveness of halal certification obligations for business actors in increasing the competitiveness of their products in the markets. The third,to analyze the positioning pattern of halal certification in the contestation of religion, market and state. These purposes were reviewed using literature review and case studies. The collecting data with observations, interviews, document review. Data were also obtained from internet sources and previous studies. The data is analyzed using the level of business competition effectiveness and critical analysis related to the contestation of religion, market and state by requiring halal certification for all entrepreneurs. The results of this study, firstly, the obligation of halal certification is present as a form of security and consumer protection from various forms of products that cannot be responsibility. Second, the level of effectiveness of halal certification for business competition of business owners depends on the market segmentation. If the target market is the national and international market, halal certification was effective in increasing market competitiveness. However, the local segmentation of halal certification has not been efficient in the process, thus denying its effectiveness. Third; halal which became the study of religion turned into a study of the market and the state, so that market contestation became dominant and led to repression by the state. Thus, the positioning of halal certification is no longer a religious study, but has turned into a market and state study.